2022
DOI: 10.1177/17470218221111750
|View full text |Cite
|
Sign up to set email alerts
|

Combining refutations and social norms increases belief change

Abstract: Misinformed beliefs are difficult to change. Refutations that target false claims typically reduce false beliefs, but tend to be only partially effective. In this study, a social norming approach was explored to test whether provision of peer norms could provide an alternative or complementary approach to refutation. Three experiments investigated whether a descriptive norm—by itself or in combination with a refutation—could reduce the endorsement of worldview-congruent claims. Experiment 1 found that using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 139 publications
(243 reference statements)
0
3
0
Order By: Relevance
“…This is consistent with the wider literature on the role of normative influence, in particular the bandwagon heuristic, in information evaluations (Metzger & Flanagin, 2013; Sundar, 2008). These findings serve as a proof-of-concept, and highlight the need to expand models of misinformation belief and continued influence, to more thoroughly consider the role of social factors (also see Ecker, Lewandowsky, et al, 2022; Ecker, Sanderson, et al, 2022; Vlasceanu & Coman, 2022). We note that in Experiment 2, the effect of claim endorsement on misinformation belief reduced to nonsignificant after a delay, suggesting that the role of claim endorsement on long-term beliefs may be limited.…”
Section: Discussionmentioning
confidence: 66%
“…This is consistent with the wider literature on the role of normative influence, in particular the bandwagon heuristic, in information evaluations (Metzger & Flanagin, 2013; Sundar, 2008). These findings serve as a proof-of-concept, and highlight the need to expand models of misinformation belief and continued influence, to more thoroughly consider the role of social factors (also see Ecker, Lewandowsky, et al, 2022; Ecker, Sanderson, et al, 2022; Vlasceanu & Coman, 2022). We note that in Experiment 2, the effect of claim endorsement on misinformation belief reduced to nonsignificant after a delay, suggesting that the role of claim endorsement on long-term beliefs may be limited.…”
Section: Discussionmentioning
confidence: 66%
“…3 & 4; again, see Legros & Cislaghi, 2020 ; Constantino et al, 2022 for overviews). Some of these insights have already been applied to change bad beliefs (e.g., Ecker et al, 2022 ; Gimpel et al, 2021 ). Whereas it’s beyond the scope of this paper to provide a full account of how SEN-change might happen, let me highlight two points here:…”
Section: The Essen-framework’s Implications For How Bad Beliefs Can B...mentioning
confidence: 99%
“…Likewise, a recent meta-analysis suggested that corrections are more successful when the corrected misinformation is worldview-discordant (Walter & Tukachinsky, 2020). On the other hand, findings of ineffective and backfiring corrections have proven difficult to replicate (Ecker et al, 2021; Guess & Coppock, 2020; Wood & Porter, 2019), and accumulating evidence suggests that people by and large adjust their beliefs at least somewhat when confronted with counterevidence, even if the misinformation is worldview-congruent (Aird et al, 2018; Ecker, Sanderson, et al, 2022; Nyhan et al, 2020; Swire, Berinsky, et al, 2017; Weeks, 2015).…”
Section: The Continued Influence Of Misinformation and Implications F...mentioning
confidence: 99%